دنیوی اور اخروی جزا و سزا اور عصری انسانی رویے : قرآنی تعلیمات اور سیرتِ نبویؐ کے تناظر میں تحقیقی و تجزیاتی مطالعہ: Worldly and Hereafter Rewards and Punishments and Contemporary Human Behavior: A Research and Analytical Study in the Context of Quranic Teachings and the Biography of the Prophet Muhammad (PBUH) (Al-Qamar, 2025)
The concepts of worldly and hereafter reward and punishment occupy a central position in Qur’anic discourse and the Prophetic Seerah, offering a comprehensive framework for understanding divine justice, moral accountability, and human behavior. This study critically examines how Qur’anic teachings and the life of the Prophet Muhammad (peace be upon him) collectively define the principles of accountability, highlighting the dynamic interaction between divine law and human conduct. Worldly consequences are discussed as immediate manifestations of human actions, functioning as corrective mechanisms for believers and as warnings for transgressors, while the hereafter is presented as the ultimate arena of justice where the eternal outcomes of deeds are determined. The article further analyzes the relevance of these concepts in the context of contemporary human behavior, exploring how ethical dilemmas, material pursuits, and socio-cultural transformations reflect the continuity of Qur’anic principles in the modern age. By bridging the classical Islamic framework with present-day challenges, the paper demonstrates that the Qur’anic and Prophetic model of reward and punishment remains a timeless guide for shaping moral responsibility and regulating human behavior across diverse contexts.
Keywords: Qur’an; Prophetic Seerah; Reward and Punishment; Worldly Consequences; Hereafter Accountability; Human Behavior; Divine Justice; Contemporary Challenges